(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The teaching of Islam is distinguished from other religions by its tolerance, mutual understanding, and respect for representatives of other faiths. The sacred sources of Islam – the Qurʼan and hadiths – pay special attention to this principle, dividing representatives of other religions into two categories: those who received a divinely revealed book (Ahl al-Kitab), and those who follow polytheistic beliefs such as Magianism and fire-worship. The concept of Ahl al-Kitab, meaning “People of the Book,” is the general name for the peoples to whom the heavenly Book was revealed by God, encompassing Jews (People of the Torah) and Christians (People of the Gospel). This article analyzes the place of the Ahl al-Kitab concept in Islamic religion and the lives of Muslims, and examines Qurʼanic and hadith perspectives on how Muslims should relate to the People of the Book and representatives of other religions.